2019
DOI: 10.1088/1361-665x/aafc5c
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical losses evaluation by energy-efficient method using the electrostrictive composites: experiments and modeling

Abstract: Recent directions in electromechanical conversion have explained the features of using electrostrictive polymers as will create new opportunities in sensing and energy harvester devices. At present time, the investigations of using electrostrictive polymer are starting to display its potential in energy harvesting area. However, the control of electromechanical losses is a major problem for electrostrictive polymers efficiency. The aim of this work is the identification of electromechanical conversion losses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Recently, there has been rapid proliferation of the demand for the energy harvesting technology latest devices. This technology has advanced significantly and is being adopted on a larger scale since the discovery of piezoelectric polymers in the last two decades as transducers/harvesters and as one of the main building blocks of an energy harvesting system [1][2][3]. Notably, energy harvesting technology using piezoelectric materials is one such method which exploits mechanical energy from various sources when subjected to kinetic energy such as vibrations, movements, and sounds from heat waves or motor bearing noise from aircraft wings and other sources, to convert that energy into an electric current or voltage to help mitigate energy depletion all around the globe [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been rapid proliferation of the demand for the energy harvesting technology latest devices. This technology has advanced significantly and is being adopted on a larger scale since the discovery of piezoelectric polymers in the last two decades as transducers/harvesters and as one of the main building blocks of an energy harvesting system [1][2][3]. Notably, energy harvesting technology using piezoelectric materials is one such method which exploits mechanical energy from various sources when subjected to kinetic energy such as vibrations, movements, and sounds from heat waves or motor bearing noise from aircraft wings and other sources, to convert that energy into an electric current or voltage to help mitigate energy depletion all around the globe [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Tide has been created by a structure-based piezoelectric polymer fiber capable of harvesting natural energy, including sun, rain, wind, wave, and research teams from the University of Bolton [18]. The textile will also be ready to execute energy generation operations in addition to behaviors such as sensing [19][20][21], actuating and conducting electricity [22][23][24]. Energy harvesting devices using bio materials and ceramic materials were also reported recently [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 At the current time, the category of electroactive material known as electrostrictive polymer has shown great potential for a variety of advanced applications 5,17 and maybe well appropriate for harvesting energy from vibration sources. [18][19][20][21][22][23][24][25] However, the electromechanical conversion efficiency increasing of electrostrictive polymer is reduced by the high value of polarization power. 21 To address this problem, many studies have been conducted on electrostrictive polymers to predict their energy recovery abilities.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] However, the electromechanical conversion efficiency increasing of electrostrictive polymer is reduced by the high value of polarization power. 21 To address this problem, many studies have been conducted on electrostrictive polymers to predict their energy recovery abilities. As an example, Putson et al 26 showed that the measurement of the harvested power established an improvement of the energy collecting ability when nanoparticles were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation